The Roman Bath at Parion: Historical Development and the Dating by 14C of Its Reused Phase - Yilmaz, Alper; Yilmaz, Zeynep (Forest Publishing Ltd, 2023)
Parion Roman Bath discussed here were built in the first quarter of the 2nd century AD, but new halls were added to the building and other major renovations were made during the last quarter of the 2nd century AD. After these changes, the building remained in use until the 5th century AD, with bathing activities coming to an end at some time after the middle of the 5th century AD. Later, the building was used for different purposes. During the excavation of the praefurnium of the Roman Bath in 2015, an oval-shaped lime kiln was found that was believed to have been built after the bathing activities ended in the building. The remains of wood used to burn marble were found in the firing chamber of the kiln. Samples taken from burnt wood were analyzed by the radiocarbon dating. Radiocarbon dates have been calibrated using the Extended 14C Database and the Revised Calib 3.014C Wet Calibration Program. The analysis revealed the not calibrated date of 1493 +/-67, which indicated the last phase of use of the lime kiln. The calibrated date is between 534 and 641 AD, which also constitutes the date of the finds evaluated in the study.This date constituted a "terminus ante quem" for the lime kiln. The present case study aimed to compare the date obtained as a result of the analysis and the date of the archaeological context and investigate whether the analysis results were compatible with the excavation context.
Yilmaz, Alper/0000-0002-1330-0518; Yılmaz, Zeynep/0000-0003-2201-2830
Keywords: Archaeology; Archaeometry; Radiocarbon; Roman Architecture; Roman Bath Architecture; Parion; Lime Kiln; Praefurnium